2009
DOI: 10.1890/08-1653.1
|View full text |Cite
|
Sign up to set email alerts
|

Prioritized phenotypic responses to combined predators in a marine snail

Abstract: Although many species face numerous predators in nature, the combined impact of multiple predators on the inducible defenses of prey has rarely been studied. Prey may respond with an intermediate phenotype that balances the risk from several sources or may simply respond to the most dangerous predator. I examined the separate and combined effects of the presence of shell-breaking (crabs, Cancer productus) and shell-entry (seastars, Pisaster ochraceus) predators fed conspecific snails on the defensive shell mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 53 publications
6
84
0
1
Order By: Relevance
“…Hence, when dragonflies are present, salamanders are less active, which reduces the intensity of the salamander-tadpole interactions that are necessary to induce the tadpole defense. Such modification of predator-specific inducible defenses by presence of another predator have been documented in other predator-prey systems (Teplitsky et al 2004;Hoverman and Relyea 2007;Lakowitz et al 2008;Bourdeau 2009). …”
Section: Modification By External Factorsmentioning
confidence: 65%
See 1 more Smart Citation
“…Hence, when dragonflies are present, salamanders are less active, which reduces the intensity of the salamander-tadpole interactions that are necessary to induce the tadpole defense. Such modification of predator-specific inducible defenses by presence of another predator have been documented in other predator-prey systems (Teplitsky et al 2004;Hoverman and Relyea 2007;Lakowitz et al 2008;Bourdeau 2009). …”
Section: Modification By External Factorsmentioning
confidence: 65%
“…To address this issue, one must examine how antagonistic phenotypic plasticity has coevolved and is maintained in a focal predator-prey interaction. Previous theoretical models have focused on either the inducible defense or offense and have concluded that both types of plasticity can stabilize predator-prey population dynamics (Abrams 1984(Abrams , 1992(Abrams , 1995Matsuda et al 1993Matsuda et al , 1994Matsuda et al , 1996Abrams and Matsuda 1997;Bolker et al 2003;Kondoh 2003Kondoh , 2007Ramos-Jiliberto 2003;Vos et al 2004a,b;Kopp and Gabriel 2006;DeAngelis et al 2007;Mougi and 18 Nishimura 2007, 2008a, 2009. However, few studies have specifically focused on reciprocity in plasticity for both the predator and its prey and behavioral reciprocity has received more attention than morphological reciprocity (Abrams 1992;van Baalen and Sabelis 1993;Adler and Grünbaum 1999;Kokko and Ruxton 2000;Abrams 2007;Krivan 2007;Krivan et al 2008;Mougi and Nishimura 2008b; but see Mougi and Kishida 2009).…”
Section: Reciprocity Of Antagonistic Inducible Phenotypesmentioning
confidence: 99%
“…Plastic shell responses are not limited to shell thickening via increased calcium carbonate deposition, and both marine and freshwater gastropods are capable of plastically altering different aspects of their shell shape (for example, aspect ratio; DeWitt, 1998;Hollander et al, 2006;Bourdeau, 2009). Altering shell shape may not require additional investment in shell deposition, just re-allocation of shell material to different shell locations, which could allow for the development of adaptive shell forms without the necessity for increased shell deposition in calcium-limited habitats.…”
Section: Meta-analysis and The Marine-freshwater Comparisonmentioning
confidence: 99%
“…Soft-bottom taxa are mostly absent (but see Martín-Mora et al, 1995 andDelgado et al, 2002 for examples of a species found on both rocky and softbottom substrates), as are studies involving predators that use methods other than shell breakage (but see Bourdeau, 2009 for exceptions). It is possible that gastropods living in softsediment habitats or those preyed on mainly by slow-moving shellentry predators (for example, seastars) may rely chiefly on plastic avoidance and/or escape behaviour as their antipredator defense, rather than plastic morphological defenses.…”
Section: Environmental Variability Of Marine Versus Freshwater Enviromentioning
confidence: 99%
See 1 more Smart Citation